Corporate Social Responsibility Disclousure, Media Attention, Woman on Board, and Firm Value - Natalia, Maria; Christy, Yunita; Gunawan, Yuliana (Jurnal ASET (Akuntansi Riset), 2019)
Abstract. This study aims to examine the effect of corporate social responsibility disclosure on firm value with attention media and woman on board as a mediating variable. Disclosure of Corporate Social Responsibility in this study will be measured using performance indicators from the Global Reporting Initiative (GRI) 4.1. The research sample is a manufacturing company listed on the IDX during 2017. This study refers to the research of Li et al. (2017), who found that Corporate Social Responsibility is positively related to company value. Effective corporate social responsibility very important for the development of the company in the long run because it plays a role in increasing the value of the company. This study also refers to the study of Isa and Muhammad (2015), who found that the participation of woman on board can ensure full disclosure of the implementation of corporate social responsibility.Keywords. corporate social responsibility; corporate value; woman on board; media attention; global reporting initiativeAbstrak. Penelitian ini bertujuan untuk menguji pengaruh pengungkapan tanggung jawab sosial perusahaan terhadap nilai perusahaan dengan media attention dan woman on board sebagai variabel mediasi. Pengungkapan Corporate Social Responsibility dalam penelitian ini akan diukur menggunakan indikator kinerja dari Global Reporting Initiative (GRI) 4.1. Sampel penelitian ini adalah perusahaan manufaktur yang terdaftar di BEI selama tahun 2017. Penelitian ini mengacu kepada penelitian Li et al. (2017) yang menemukan menunjukkan bahwa Corporate Social Responsibility berhubungan positif dengan nilai perusahaan. Corporate Social Responsibility yang efektif sangat penting untuk pengembangan perusahaan dalam jangka panjang karena berperan dalam meningkatkan nilai perusahaan. Penelitian ini juga mengacu kepada penelitian Isa dan Muhammad (2015) yang menemukan bahwa partisipasi woman on board dapat memastikan pengungkapan penuh dari pelaksanaan tanggung jawab social perusahaan.Kata kunci. tanggung jawab sosial perusahaan; nilai perusahaan; woman on board; media attention; global reporting initiative